Evaluation of Quantification of HIV-1 RNA Viral Load in Plasma and Dried Blood Spots by Use of the Semiautomated Cobas Amplicor Assay and the Fully Automated Cobas Ampliprep/TaqMan Assay, Version 2.0, in Kisumu, Kenya - Ouma, Kenneth N. (American Society for Microbiology, 2013)
In Kenya, HIV-1 viral load monitoring is commonly performed with the Cobas Amplicor using plasma specimens. Interest is growing in transitioning to real-time PCR (RT-PCR), such as the Cobas Ampliprep/Cobas TaqMan (CAP/CTM), using dried blood spots (DBS). Before implementation, direct evaluation of the two assays using DBS field specimens is required. This study compares the sensitivity, specificity, negative and positive predictive values (NPV and PPV, respectively), concordance, and agreement between HIV-1 viral load measurements using plasma and DBS specimens obtained from 512 HIV-1-infected pregnant females enrolled in the Kisumu Breastfeeding Study and tested with the Cobas Amplicor and CAP/CTM assays. The sensitivity and NPV of viral load detection in DBS specimens were higher with CAP/CTM (sensitivity, 100%; 95% confidence interval [CI], 99.1 to 100.0%; NPV, 100%; 95% CI, 59.0 to 100.0%) than the Cobas Amplicor (sensitivity, 96.6%; 95% CI, 94.3 to 98.1%; NPV, 58.8%; 95% CI, 40.7 to 75.4%). The PPVs were comparable between both assays when using DBS. The specificity of viral load detection in DBS specimens was lower with CAP/CTM (77.8%; 95% CI, 40.0 to 97.2%) than that of the Cobas Amplicor (95.2%; 95% CI, 76.2 to 99.9%). Good concordance and agreement were observed when paired plasma and DBS specimens were tested with both assays. Lower specificity with the CAP/CTM is likely due to proviral HIV-1 DNA amplification and lower detection limits with RT-PCR. However, the CAP/CTM has better sensitivity and higher throughput than the Cobas Amplicor. These findings suggest that DBS may be a suitable alternative to plasma when using RT-PCR, which could increase access to viral load monitoring in resource-limited settings.